Defective double-metal MOF photocatalyst for photocatalytic conversion of polystyrene waste plastic and preparation method and application thereof
Patent Information
- Application Number
- CN202611207582.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-09
AI Technical Summary
[0023](1) 本发明构建了一种缺陷型Zr/Ti双金属MOF光催化剂,通过Ti金属组分调控MOF局部配位环境,促进氧空位缺陷形成,并结合表面酸性功能化,实现双金属配位环境、缺陷结构和酸性位点的协同调控。
Smart Images

Figure CN122875295A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of industrial catalysis and waste plastic resource recycling technology, and relates to a defective bimetallic MOF photocatalyst for photocatalytic conversion of polystyrene waste plastics, its preparation method and application. Background Technology
[0002] Polystyrene is a widely used single-use plastic, but its strong chemical inertness and difficulty in natural degradation lead to the accumulation of large amounts of waste in the environment, placing enormous pressure on the ecological environment. Traditional landfill and incineration methods waste resources and produce harmful gases, failing to meet the needs of sustainable development. Photocatalysis, using solar energy as an energy source, has advantages such as mild conditions and green sustainability, and is considered one of the effective ways to recycle waste plastics. Aromatic carbonyl compounds such as benzoic acid, benzaldehyde, and acetophenone are important industrial intermediates, widely used in pharmaceuticals, food, and polymer materials. Chemically recycling waste polystyrene plastics through photocatalysis into aromatic carbonyl compounds can realize the transformation from "waste" to "high-value-added fine chemicals," opening a promising path for its high-value utilization.
[0003] Polystyrene molecules possess a stable CCC backbone structure, posing a challenge to its transformation process. Traditional photocatalytic materials such as TiO2 and ZnO typically have relatively stable crystal structures, but their active site types are limited, making it difficult to simultaneously meet the multiple requirements of polymer adsorption, oxygen molecule activation, and selective oxidation. In contrast, MOF materials possess open metal nodes and tunable organic ligand environments, allowing for the construction of multifunctional synergistic active centers through metal component adjustment, defect engineering, and post-modification strategies, providing new possibilities for the selective transformation of complex organic molecules. However, single-metal MOF materials exhibit limited catalytic activity in photocatalytic reactions, making it difficult to achieve effective activation and subsequent oxidation of the polymer's inert CCC backbone. By introducing a second metal component into MOFs to construct bimetallic MOF structures, the synergistic regulatory effects between different metal components can improve the electronic structure and catalytic performance of the materials. For example, introducing a Ti component into a Zr-based MOF creates an oxygen vacancy defect structure, promoting the activation of oxygen molecules; further modification of acidic active sites can promote the adsorption and activation of polystyrene segments, facilitating the oxidative cleavage of the polymer backbone and subsequent oxidation reactions. However, no research has been reported on achieving selective oxidative chain scission of polystyrene waste plastics through synergistic regulation of the local coordination environment, defect structure, and surface acidic sites of bimetallic MOFs. Therefore, developing a defective Zr / Ti bimetallic MOF photocatalytic material and achieving its promotion of high-value conversion of polystyrene waste plastics under mild conditions is a pressing technical problem to be solved in this field. Summary of the Invention
[0004] The purpose of this invention is to provide a defect-type Zr / Ti bimetallic MOF photocatalyst for the photocatalytic conversion of polystyrene waste plastics, solving the problems of difficult activation of polystyrene segments, low oxygen molecule activation efficiency, and insufficient selectivity for oxidation chain scission in existing photocatalytic materials. By introducing a Ti component into the metal coordination environment of the MOF, the local electronic structure is modulated and the formation of oxygen vacancy defects is promoted. Furthermore, surface functionalization modification is used to construct acidic active sites on the surface, achieving synergistic regulation of the bimetallic coordination environment, defect structure, and acidic sites, thus promoting the adsorption activation and oxidation chain scission of polystyrene molecules. The invention also provides a method for preparing this photocatalyst and its application in the conversion of polystyrene waste plastics.
[0005] To achieve the above objectives, the present invention provides the following technical solution: On one hand, the present invention provides a defect-type bimetallic MOF photocatalyst, which comprises a Zr / Ti bimetallic MOF material. The Zr / Ti bimetallic MOF uses a carboxyl-containing aromatic organic ligand as its framework, with Zr and Ti as metal components. The Ti component is introduced into the MOF structure, forming a Zr / Ti bimetallic coordination environment together with Zr, resulting in an oxygen vacancy defect structure in the material. Simultaneously, the surface of the material is functionalized to introduce acidic sites containing trifluoromethanesulfonate structures.
[0006] In a preferred embodiment of the present invention, the organic ligand is 1,3,5-tris(4-carboxyphenyl)benzene, and the acidic site containing the trifluoromethanesulfonate structure can be formed by surface functionalization treatment of trimethylsilyl trifluoromethanesulfonate.
[0007] In this invention, the introduction of the Ti metal component helps to modulate the electronic structure of the metal coordination environment of the Zr-based MOF and promotes the formation of oxygen vacancy defects. These defect structures facilitate the migration of photogenerated carriers and the interfacial electron transfer process. Simultaneously, by functionalizing the surface with acidic ions (containing trifluoromethanesulfonate), acidic active sites are constructed on the material surface, enhancing the adsorption and activation capabilities of polystyrene segments. Therefore, the synergistic effect between the bimetallic coordination environment, the defect structure, and the surface acidic sites promotes the oxidative chain scission process of polystyrene.
[0008] This invention provides a method for preparing the above-mentioned bimetallic MOF photocatalyst, comprising the following steps:
[0009] S1. Zr salt and carboxyl-containing aromatic organic ligands are mixed in an organic solvent and reacted under solvothermal conditions to prepare Zr-based MOF precursors.
[0010] S2. The Zr-based MOF precursor obtained in step S1 is mixed with the Ti source in a solvent and reacted under solvothermal conditions to introduce the Ti component into the coordination environment of the Zr-based MOF, thereby regulating the local coordination environment of the material and obtaining the Zr / Ti bimetallic MOF material.
[0011] S3. The Zr / Ti bimetallic MOF material obtained in step S2 is subjected to acidification treatment to remove at least some of the terminal coordination species and form or expose surface hydroxyl groups.
[0012] S4. Under an inert atmosphere, the product obtained in step S3 is dispersed in an anhydrous organic solvent, and trimethylsilyl trifluoromethanesulfonate is added to react, so that acidic active sites containing trifluoromethanesulfonate structures are formed on the surface of the Zr / Ti bimetallic MOF material. After washing and drying, the target bimetallic MOF photocatalyst is obtained.
[0013] Based on the above technical solution, preferably:
[0014] In step S1, the Zr salt is zirconium tetrachloride, and the organic ligand is preferably 1,3,5-tris(4-carboxyphenyl)benzene; the solvothermal reaction temperature is 90–150 °C, and the reaction time is 24–72 hours.
[0015] In step S2, the titanium source is selected from at least one of metallocene titanium halides and titanium halides; more specifically, the metallocene titanium halide is preferably titanium dichlorodicyclopentadiene, and the titanium halide is preferably titanium tetrachloride; most preferably, the titanium source is titanium dichlorodicyclopentadiene. The amount of titanium source added is 0.10–2.41 mmol, preferably 0.5–0.7 mmol; the titanium introduction reaction temperature is 80–130°C, and the reaction time is 2–15 hours.
[0016] In step S3, the acidification treatment is carried out using hydrochloric acid with a concentration of 0.8–1.2 mol / L, a reaction temperature of 90–110°C, and a reaction time of 8–18 hours.
[0017] In step S4, the anhydrous organic solvent is anhydrous toluene, and the surface functionalization treatment is carried out under an inert atmosphere.
[0018] This invention also provides the application of the above-mentioned bimetallic MOF photocatalyst in the photocatalytic conversion of polystyrene waste plastics. Specifically, the bimetallic MOF photocatalyst is mixed with polystyrene waste plastics and an organic reaction medium, and reacted under oxygen-containing atmosphere and light conditions to induce oxidative chain scission in polystyrene, generating aromatic carbonyl small molecule products such as benzoic acid, benzaldehyde, and acetophenone; when a chlorine-containing organic solvent (such as dichloromethane) is used, the product may also contain 2-chloroacetophenone.
[0019] The polystyrene includes polystyrene of different molecular weights and actual polystyrene waste plastics.
[0020] The reaction medium is a mixed solvent of acetonitrile and dichloromethane;
[0021] The reaction is carried out at a temperature not exceeding 40 °C, under normal pressure, in an oxygen-containing atmosphere, and under visible light or simulated sunlight.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) This invention constructs a defect-type Zr / Ti bimetallic MOF photocatalyst. By regulating the local coordination environment of MOF through Ti metal components, the formation of oxygen vacancy defects is promoted. Combined with surface acid functionalization, the bimetallic coordination environment, defect structure and acid sites are synergistically regulated.
[0024] (2) Mild reaction conditions. The photocatalytic conversion of polystyrene is carried out at room temperature, atmospheric pressure and oxygen atmosphere, without the need for additional heating and pressurization or the use of strong oxidants. Compared with traditional thermal pyrolysis, it has low energy consumption and safe operation.
[0025] (3) High value and universality. Waste polystyrene plastics are converted into various aromatic carbonyl small molecules, rather than being simply mineralized, thus realizing the resource utilization of waste plastics. The total yield of aromatic carbonyl small molecules in standard polystyrene can reach 40.98%, and the weight-average molecular weight M w The carbon dioxide content can be reduced from 168.4 kDa to below 1 kDa, a decrease of over 99%. This technology is not only applicable to standard polystyrene, but also has the same effect on recycled waste polystyrene foam, demonstrating its versatility. Attached Figure Description
[0026] Figure 1 A bar chart comparing the photocatalytic conversion performance of polystyrene by catalysts obtained with different amounts of titanium dichlorophenocene (Examples 1-4).
[0027] Figure 2 Gel permeation chromatography (GPC) chromatograms of solid residues after photocatalytic conversion of polystyrene under different catalyst systems (Examples 1, 10 and Comparative Examples 1-3).
[0028] Figure 3 This is a performance data table for different catalysts.
[0029] Figure 4 The XPS full spectrum and O 1s fine spectrum of the sample obtained in Example 1 (Zr / Ti-BTB-OTf) are compared with those of the sample obtained in Comparative Example 1 (Zr-BTB-OTf).
[0030] Figure 5 The image shows the electron paramagnetic resonance (EPR) detection results of the sample (Zr / Ti-BTB-OTf) obtained in Example 1 and the sample (Zr-BTB-OTf) obtained in Comparative Example 1.
[0031] Figure 6The image shows the gas chromatography-mass spectrometry (GC-MS) results of the reaction solution after the photocatalysis experiment in Example 1. Detailed Implementation
[0032] Example
[0033] It should be understood that, without altering the technical concept of this invention, those skilled in the art can also introduce the Ti component through methods such as in-situ assembly, and these variations should all be considered to fall within the scope of protection of this invention. Furthermore, those skilled in the art can, based on common knowledge and conventional experiments, appropriately adjust the amount of Ti source, reaction temperature, reaction time, solvent dosage, and surface functionalization conditions according to actual materials and preparation requirements. Therefore, the specific material parameters in the examples should not be considered as limitations on the scope of protection of this invention.
[0034] Example 1
[0035] A method for preparing a Zr / Ti bimetallic MOF photocatalyst includes the following conditions and steps:
[0036] Preparation of S1 and Zr-BTB precursors: 101.8 mg of zirconium tetrachloride and 125 mg of 1,3,5-tris(4-carboxyphenyl)benzene were ultrasonically dispersed in 25 mL of N,N-dimethylformamide, respectively. The two solutions were then mixed. Subsequently, 1.5 mL of deionized water and 8.5 mL of formic acid were added, and the mixture was ultrasonicated for 5 min. The mixture was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene and placed in a drying oven at 120 ℃ for 48 h. After the reaction was complete, the mixture was cooled to room temperature, centrifuged, and washed several times with N,N-dimethylformamide and methanol sequentially. The precipitate was then vacuum dried at 80 ℃ for 12 h to obtain Zr-BTB.
[0037] S2. Constructing a Zr / Ti bimetallic MOF by introducing Ti metal components: 160 mg of the Zr-BTB precursor obtained in step S1 and 0.6 mmol of dichlorotitanium thiocarbamate were added to 50 mL of N,N-dimethylformamide. After stirring for 1 h, the resulting suspension was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene and placed in a 120 ℃ drying oven for 4 h. After the reaction was completed, the mixture was cooled to room temperature, and the precipitate was separated by centrifugation and washed multiple times with N,N-dimethylformamide, chloroform, and methanol, respectively. The product was then vacuum dried at 80 ℃ for 12 h to obtain Zr / Ti-BTB.
[0038] S3. Acidification treatment: 20 mg of the Zr / Ti-BTB sample obtained in step S2 was added to 50 mL of dilute hydrochloric acid (1 M), and the mixture was stirred at 100 °C for 18 h to remove some of the terminal formate. After the reaction was completed and cooled to room temperature, the product was centrifuged to obtain a white solid, which was washed several times with N,N-dimethylformamide and acetonitrile. The product was dried overnight in a vacuum oven at 80 °C to obtain Zr / Ti-BTB-OH.
[0039] S4. Surface Functionalization: 160 mg of the Zr / Ti-BTB-OH sample obtained in step S3 was collected and dispersed in 12 mL of anhydrous toluene under an inert gas protection. Then, 1.08 mL of trimethylsilyl trifluoromethanesulfonate was slowly added dropwise to the suspension, and the mixture was heated and stirred at 80 °C for 12 h. After the reaction was completed, the product was washed several times with anhydrous toluene and chloroform to remove soluble substances. The product was dried overnight in a vacuum oven at 60 °C to obtain the target catalyst (labeled Zr / Ti-BTB-OTf).
[0040] The catalyst prepared by the above method was used for the photocatalytic conversion of waste polystyrene plastics, and the results are shown in the figure. Figure 1 , Figure 2 and Figure 3 The experimental procedure included the following conditions and steps: 5 mg of catalyst and 0.5 mmol (based on benzene ring units) of commercially available polystyrene particles (weight average molecular weight M). w = 168.4 kDa), 10 mL of acetonitrile / dichloromethane (volume ratio 2:3) mixed solvent was added to a quartz reaction flask, an oxygen bulb was connected, and the flask was placed in a multi-site bottom-illuminated white LED reactor. Magnetic stirring and cooling water were turned on, and the reaction temperature was controlled at 25±2℃ for 48 hours under light irradiation. After the reaction, the catalyst and reaction solution were separated by filtration. The separated reaction solution was further filtered using a filter membrane, and nitrobenzene was added as an internal standard. 1.5 mL of the above solution was analyzed by gas chromatography-mass spectrometry (GC-MS). Taking benzoic acid as an example, the molar yield and selectivity were calculated according to the following formula:
[0041] ;
[0042] ;
[0043]
[0044] The remaining reaction solution was rotary evaporated to obtain a solid residue, which was washed, dried, dissolved in tetrahydrofuran, and its molecular weight was determined by GPC.
[0045] Example 2
[0046] The catalyst was prepared according to the method in Example 1, except that the amount of titanium dichlorodicyclopentadiene added in step S2 was adjusted to 0.10 mmol, while the other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 1 , Figure 2 and Figure 3 .
[0047] Example 3
[0048] The catalyst was prepared according to the method in Example 1, except that the amount of titanium dichlorodicyclopentadiene added in step S2 was adjusted to 0.18 mmol, while the other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 1 , Figure 2 and Figure 3 .
[0049] Example 4
[0050] The catalyst was prepared according to the method in Example 1, except that the amount of titanium dichlorodicyclopentadiene added in step S2 was adjusted to 2.41 mmol, while the other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 1 , Figure 2 and Figure 3 .
[0051] Example 5
[0052] The catalyst was prepared according to the method of Example 1, except that in step S1, an equimolar amount of 1,3,5-tris(4′-carboxybiphenyl)benzene with a biphenyl extended structure was used instead of 1,3,5-tris(4-carboxyphenyl)benzene, while the other conditions remained unchanged. The resulting catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 3 .
[0053] Example 6
[0054] The catalyst was prepared according to the method in Example 1, except that in step S1, an equimolar amount of methyl-modified 1,3,5-trimethyl-2,4,6-tris(4-carboxyphenyl)benzene was used instead of 1,3,5-tris(4-carboxyphenyl)benzene, while the other conditions remained unchanged. The resulting catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 3 .
[0055] Example 7
[0056] The catalyst was prepared according to the method in Example 1, except that titanium tetrachloride was used instead of titanium dichloropentane in S2, while the other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 3 .
[0057] Example 8
[0058] The catalyst was prepared according to the method in Example 1, except that the polystyrene used in the catalytic reaction had a weight-average molecular weight of 107.5 kDa, while all other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 3 .
[0059] Example 9
[0060] The catalyst was prepared according to the method in Example 1, except that the polystyrene used in the catalytic reaction had a weight-average molecular weight of 280.2 kDa, while all other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 3 .
[0061] Example 10
[0062] The catalyst was prepared according to the method in Example 1, except that the polystyrene used in the catalytic reaction was derived from actual waste polystyrene foam with a weight-average molecular weight of 166.4 kDa, while all other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 2 and Figure 3 .
[0063] Comparative Example 1
[0064] This comparative example prepared a Ti-free catalyst (labeled Zr-BTB-OTf). The preparation process was identical to that of Example 1, except that the Ti component introduction step described in S2 was omitted. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown below. Figure 1 , Figure 2 and Figure 3 .
[0065] Comparative Example 2
[0066] The catalyst was prepared according to the method in Example 1, except that the catalytic reaction was carried out under light-shielded conditions, while all other conditions remained unchanged. The obtained catalyst was used for the photocatalytic conversion of polystyrene, and the experimental results are shown in [Figure 1]. Figure 2 and Figure 3 .
[0067] Comparative Example 3
[0068] The photocatalytic experiment was conducted according to Example 1, except that no catalyst was used during the catalytic reaction, while all other conditions remained unchanged. The experimental results are shown below. Figure 2 and Figure 3 .
[0069] XPS was used to analyze the samples obtained in Example 1 and Comparative Example 1, such as... Figure 4 As shown, compared with the Zr-BTB-OTf sample obtained in Comparative Example 1, the Zr / Ti-BTB-OTf sample obtained in Example 1 showed a characteristic peak of Ti 2p in the full spectrum, confirming the presence of the Ti component; further peak fitting of the O 1s fine spectrum revealed the appearance of characteristic peaks attributed to oxygen vacancies, suggesting the presence of oxygen vacancy defect structures in the sample of Example 1. EPR detection was performed, and the results are as follows... Figure 5 As shown. Compared with the Zr-BTB-OTf sample obtained in Comparative Example 1, the Zr / Ti-BTB-OTf sample obtained in Example 1 showed a stronger oxygen vacancy signal peak at g=2.0031. Based on the comparison sample, it is inferred that the introduction of Ti component contributes to the formation of oxygen vacancy defects. As the illumination time increased to 5 min, the peak intensity of Zr / Ti-BTB-OTf increased significantly, while Zr-BTB-OTf showed little change. In addition, a new sharp peak appeared in Zr / Ti-BTB-OTf at g=1.987, showing the influence of Ti. 3+ Based on the typical characteristics, it is speculated that the Ti site can serve as a photogenerated electron transfer center.
[0070] The sample obtained in Example 1 was used for photocatalysis experiments, and GC-MS analysis was performed. Figure 6 It can detect characteristic peaks and corresponding mass spectra of aromatic carbonyl products such as benzaldehyde, acetophenone, and benzoic acid. In addition, the characteristic peak of 2-chloroacetophenone can be clearly detected, and this product is included in the total yield of aromatic carbonyl small molecules. Specific performance data are as follows: Figure 1 and Figure 3 As shown, the total yield of aromatic carbonyl small molecules reached 40.98%, indicating that the catalytic system can effectively cleave the PS backbone and achieve selective oxidation. Further investigation was conducted on the effect of Ti feed rate on catalytic performance. Figure 1 It was found that as the amount of titanium dichlorodichloropentane added increased from 0.00 mmol (Comparative Example 1) to 0.6 mmol (Example 1), the total yield of aromatic carbonyl small molecules gradually increased from 16.02% to 40.98%; however, the activity decreased significantly when the amount was further increased to 2.41 mmol. It is speculated that the introduction of an appropriate amount of Ti is beneficial to the formation of oxygen vacancies and charge separation, but excessive Ti may become a recombination center or block the pores. Therefore, the amount of Ti added in this invention needs to be controlled within a suitable range.
[0071] Regarding the catalyst composition, Examples 5 and 6 used biphenyl-extended or methyl-substituted aromatic tricarboxylic acid ligands, and Example 7 used titanium tetrachloride instead of titanium dichlorodicenocene. All the resulting catalysts exhibited considerable catalytic activity. Figure 3This indicates that the method described in this invention has universality for similar aromatic polycarboxylic acid ligands and different titanium sources. Regarding substrate adaptability, Examples 8-9 showed good degradation effects on PS with different molecular weights (107.5 kDa and 280.2 kDa); in particular, Example 10 used actually recycled PS waste foam (M... w Even at a power density of 166.4 kDa, it can still achieve efficient conversion, proving its application potential in real-world waste plastic treatment scenarios.
[0072] To assess the degree of polymer backbone breakage, GPC was used to analyze the molecular weight of the solid residue after the reaction. Figure 2 and Figure 3 The results showed that the M of the polystyrene after the reaction in Example 1 was... w The molecular weight of polystyrene decreased significantly from an initial 168.4 kDa to 0.9 kDa, a reduction of over 99%, indicating that the polystyrene polymer underwent significant chain scission or degradation in the catalytic system of this invention. Although Comparative Example 1 also resulted in partial polymer chain scission, the yield of aromatic carbonyl products was significantly lower than in Example 1, demonstrating that Ti-induced defect structures are crucial for promoting selective oxidation after oxidative chain scission. Furthermore, the changes in PS molecular weight were relatively small under Comparative Example 2 (light-protected) and Comparative Example 3 (no catalyst) conditions. These results fully demonstrate that Ti-induced oxygen vacancy defects, photogenerated charge separation, and surface acidic sites are all indispensable, and their synergistic effect is key to achieving efficient PS backbone scission. In addition, the molecular weight of the polystyrene solid residue in Example 10 (actual waste polystyrene foam) decreased significantly from 166.4 kDa to below 1 kDa, further confirming the good application potential of this catalyst system for actual waste polystyrene plastics.
Claims
1. A defect-type bimetallic MOF photocatalyst for photocatalytic conversion of waste polystyrene plastics, characterized in that, The photocatalyst comprises a Zr / Ti bimetallic MOF; the Zr / Ti bimetallic MOF is composed of metal components Zr and Ti and organic ligands, wherein the organic ligands are carboxyl-containing aromatic organic ligands; the Zr / Ti bimetallic MOF has an oxygen vacancy defect structure; and the surface of the Zr / Ti bimetallic MOF is functionalized to form acidic sites containing trifluoromethanesulfonate structures.
2. The bimetallic MOF photocatalyst according to claim 1, characterized in that, The organic ligand is 1,3,5-tris(4-carboxyphenyl)benzene (BTB).
3. The bimetallic MOF photocatalyst according to claim 1, characterized in that, The acidic sites containing the trifluoromethanesulfonate structure are formed by surface functionalization using trimethylsilyl trifluoromethanesulfonate.
4. A method for preparing the bimetallic MOF photocatalyst according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Preparation of Zr-based MOF precursors; S2. Introduce Ti metal component into the MOF precursor containing Zr metal component; S3. The Zr / Ti bimetallic MOF material is subjected to acidification treatment to remove terminal coordination species and form or expose surface hydroxyl groups. S4. The sample after acidification is subjected to surface functionalization treatment to form acidic sites containing trifluoromethanesulfonate structures on its surface, thereby obtaining the bimetallic MOF photocatalyst.
5. The method according to claim 4, characterized in that: The Zr-based MOF precursor mentioned in step S1 is Zr-BTB; Zr-BTB is prepared by a solvothermal reaction of zirconium tetrachloride and 1,3,5-tris(4-carboxyphenyl)benzene.
6. The method according to claim 4, characterized in that, In step S2, Ti is introduced into the Zr-based MOF coordination environment through a post-synthetic modification method; the titanium source is selected from one or more of metallocene titanium halides and titanium halides.
7. The method according to claim 6, characterized in that, The metallocene titanium halide is titanium dichlorodicyclopentadiene, and the titanium halide is titanium tetrachloride.
8. The method according to claim 4, characterized in that: Step S3 involves acidification with hydrochloric acid solution; Step S4 is carried out under an inert atmosphere and anhydrous conditions.
9. An application of the bimetallic MOF photocatalyst according to claim 1 in the conversion of polystyrene waste plastics, characterized in that, Waste polystyrene plastic, the bimetallic MOF photocatalyst, and an organic reaction medium are mixed and reacted under oxygen-containing atmosphere and light conditions to cause oxidative chain scission of polystyrene, generating aromatic carbonyl small molecule products.
10. The application according to claim 9, characterized in that, The reaction temperature does not exceed 40 °C, and the reaction atmosphere is an oxygen atmosphere; the reaction medium is a mixed solvent of acetonitrile and dichloromethane; the polystyrene includes polystyrene materials of different molecular weights and polystyrene materials derived from actual waste plastic products; the aromatic carbonyl small molecule product includes one or more of benzoic acid, benzaldehyde, acetophenone, and 2-chloroacetophenone.